Hydrogen, a Novel Therapeutic Molecule, Regulates Oxidative Stress, Inflammation, and Apoptosis - Tian, Yan; Zhang, Yafang; Wang, Yu; Chen, Yunxi; Fan, Weiping; Zhou, Jianjun; Qiao, Jing; Wei, Youzhen (Frontiers in Physiology, 2021)
Molecular hydrogen (H2) is a colorless and odorless gas. Studies have shown that H2 inhalation has the effects of anti-oxidation, anti-inflammation and anti-apoptosis in many animal studies and clinical trials, and its application is recommended in the novel coronavirus pneumonia treatment guidelines in China recently. H2 has a relatively small molecular mass, which help it quickly spread and penetrate cell membranes to exert a wide range of biological effects. It may play a role in the treatment and prevention of a variety of acute and chronic inflammatory diseases, such as acute pancreatitis, sepsis, respiratory disease, cardiovascular and cerebrovascular diseases, autoimmunity diseases and so on. H2 is primarily administered via inhalation, drinking H2-rich water, or injection of H2 saline. It may participate in the anti-inflammatory and antioxidant activity, mitochondrial energy metabolism, endoplasmic reticulum stress, immune system regulation and cell death (apoptosis, autophagy and pyroptosis) through annihilating excess reactive oxygen species production and modulating nuclear transcription factor, which has therapeutic potential for many systemic diseases. However, the underlying mechanism of H2 has not yet been fully revealed. Owing to its safety and potential efficacy, H2 has promising potential for clinical use against many diseases. This review will demonstrate the role of H2 in anti-oxidative, anti-inflammatory and anti-apoptotic effects and its underlying mechanism, providing strategies for the medical application of H2 for various diseases.